Treatment of Femoral Shaft Fractures in Patients with Klippel-Trénaunay Syndrome: A Report of 2 Cases. Issue 3 (July 2021) - Mahjoub, Adel; Gilbert, Grace; Turkula, Stefan; Mendez, Gregory; Graf, Kenneth; Kim, Tae Won B.
Abstract : Cases: Long-bone fractures in patients with Klippel-Trénaunay syndrome (KTS), a rare disorder of the venous, lymphatic, and capillary system, are difficult to treat with many complications. Two patients diagnosed with KTS presented with closed femoral shaft fractures after low-energy falls. Conservative treatment, open reduction internal fixation, and intramedullary nailing resulted in painful nonunions. Ultimately, both patients achieved pain relief and the ability to ambulate after en bloc resection and reconstruction. Conclusions: These cases demonstrate the challenges in achieving bony union when treating long-bone fractures in KTS. The feasibility of undergoing extensive resection and reconstruction to regain function is best approached with a multidisciplinary team.